FOCUS ON ACHIEVING THE GOALS OF SUSTAINABLE DEVELOPMENT AS A LEADING TENDENCY IN THE PROFESSIONAL TRAINING OF CIRCULAR ECONOMY SPECIALISTS - Oleksii Sysoiev (Неперервна професійна освіта: теорія та практика)
The article examines the leading trend in the professional training of circular economy specialists in the Republic of Finland, the Republic of Poland and Ukraine - the focus on the implementation of the Sustainable Development Goals; the author concludes that the training of circular economy specialists and the implementation of the Sustainable Development Goals are interconnected and interdependent. It is shown that the training of such specialists brings each country closer to the implementation of the 17 Sustainable Development Goals, which were defined in September 2015 at the 70th session of the UN General Assembly in New York at the UN Summit on Sustainable Development, and fully meets the motivational criterion for comparing trends in professional training in different countries, which reflects the interdependence of sustainable development of society and the development of economic science and professional training of specialists in new specialties, realized at the State and scientific levels. This criterion also characterizes the degree of public awareness and motivation of citizens regarding the need to fulfill the goals of sustainable development and the threats that arise when they are neglected.